Emotional impact of using different sensory modalities for autobiographical activation: a systematic review and meta-analysis - Fernández-Pérez, Dolores; Navarro-Bravo, Beatriz; Toledano-González, Abel; Ricarte, Jorge Javier; Latorre-Postigo, Jose Miguel; Ros, Laura (Frontiers in Psychology, 2025)
IntroductionTo the best of our knowledge, no previous work has synthesized the efficacy of MIPs based on the retrieval of AMs in relation to a wide range of both basic and complex emotions. This gap highlights the need to better understand how these interventions influence emotional states.MethodologyAccordingly, we conducted a systematic review of the literature and, when data were sufficient, a meta-analysis of pre-post changes in affective state. Our aim was to identify the most effective procedures for manipulating mood within empirical studies, and to develop a coherent framework to organize and interpret the efficacy of these types of MIPs, providing a foundation for future research.ResultsThe existing evidence is fragmented across heterogeneous protocols and lacks a unified quantitative synthesis. This fragmentation underscores the necessity of a systematic review and meta-analysis, which the present article undertakes to address.DiscussionFurthermore, we consider the growing interest in the field of “memory therapy”, given its clinical benefits in helping individuals access past events and allowing them to relive experiences and their associated emotions. This area holds promise for enhancing emotional regulation and therapeutic outcomes.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42021249072, identifier: CRD42021249072.